Mechanical, degradation and drug-release behavior of nano-grained Fe-Ag composites for biomedical applications - Sharipova A. R. Aliya Rashitovna; Swain S. K. Sanjaya; Gotman I. Irina; Starosvetsky D.; Psakhie S. G. Sergey Grigorievich; Unger R. E. Ronald; Gutmanas E. Elazar (2018, 2018)
Title screen